The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/491047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air-Polishing on Titanium Surfaces, Biofilm Removal, and Biocompatibility: A Pilot Study

Abstract: Purpose. The aims of this in vitro study were to evaluate morphological changes induced by glycine powder air-polishing on titanium surfaces, biofilm removal, and biocompatibility. Material and Methods. Titanium grade IV discs were allocated into two groups: (1) discs without biofilm and (2) discs for Streptococcus mutans biofilm formation. Discs in each group were further subdivided into (a) no treatment and (b) air-polishing treatment with glycine powder. Discs were characterized by scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
(46 reference statements)
1
28
0
Order By: Relevance
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 48 selected studies have been reported in chronological order in Table . It is noteworthy to mention that out of 48 included studies, only 11 studies employed devices to standardize the decontamination procedure and avoid the clinician erroneous, and only one study used a phantom head to simulate clinical conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay has been used in many past studies. 63,185,186 The study followed on from the work presented in Chapter 3 which examined the effects of instruments on Ti surfaces only (no biofilm), and likewise will use SEM to assess surface damage produced during biofilm removal.…”
Section: Titanium Brushesmentioning
confidence: 99%
“…221,222 From the work in this thesis and other published studies, it appears that Er:YAG lasers, glycine particles, citric acid and electrolysis are promising areas to explore further, since these treatments are likely to either enhance biocompatibility, or at the very least, will not lower the surface energy. 93,165,186,223 From the work described in this thesis (as summarized Table 7.3), a suggested combination approach would be as follows when a purely closed debridement approach was to be used:…”
Section: Combination Approachesmentioning
confidence: 99%